Implementasi Strategi Manajemen Pendidikan Dalam Mengembangkan Kualitas Pengajaran di RA Nurul Falah - Nurhayati; Nurjanah; Siska, Rara; Amelia, Rosa; Permana, Hinggil (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
This study examines the implementation of educational management strategies in developing teaching quality in RA Nurul Falah Sunyar Karawang. The educational management strategies implemented include competency-based curriculum planning, teacher professional development, and periodic evaluation and supervision. The main focus of this research is to analyze the effectiveness of these strategies in developing teaching quality and their impact on the teaching and learning process in the RA. The research method used is a case study with a qualitative approach. The subjects of this research were several teachers and the principal of RA Nurul Salah Sunyar Karawang. Data collection techniques were carried out using observation, interview, and documentation methods. The results showed that the implementation of planned and systematic education management strategies was able to significantly improve teaching quality, with indicators of increased teacher competence, the application of more innovative teaching methods, and increased parent and student satisfaction. This study provides recommendations for further development of managerial strategies to continue developing teaching quality in RA Nurul Falah Sunyar and similar educational institutions.